EFFECT OF FEED PROTEIN VARIATIONS ON CULTURE PERFORMANCE AND NUTRITION PROFILE OF TILAPIA (OREOCHROMIS NILOTICUS) IN A BIOFLOCK CULTIVATION SYSTEM - H. Basri, A.
The success of the biofloc system is determined by the ratio of carbon to nitrogen (C/N ratio) which is suitable to stimulate the growth of heterotrophic bacteria and maintain the balance of the microbial community and the quality of the culture water. The main source of nitrogen input in a closed biofloc system is feed, the protein content in the feed have a role in the growth of tilapia and also affect the value of the C/N ratio of the culture water. The purpose of this study was to determine the effect of variations in feed protein on the culture performance and nutritional profile of tilapia in the biofloc system. This research was conducted in three stages, namely: (1) Preparation of a closed biofloc system, (2) The process of cultivating tilapia in the biofloc system using three types of feeds with different crude protein content, namely 22%, 26%, and 30%, and (3) Measurement of the nutritional profile of tilapia in a biofloc system given three types of feed with different protein content. The number of fish stocked was 75 fish/m3 with average initial weight 37.7±11.1 g. Cultivation was carried out for 90 days using 1000 L cylindrical fiber tank with three replicates per treatment. Molasses was added to maintain the ratio C/N=15 for each treatment. Parameters observed included physico-chemical parameters of water quality (temperature, DO, pH, NH4+, NO2-), biological parameters (absolute growth, specific growth rate, survival rate, biomass, feed conversion ratio), and fish nutritional profile (proximate analysis, amino acid profile, fatty acid profile). Data were analyzed using variance (ANOVA) at the 95% confidence level. The result showed that variations in the use of feed protein content have different impacts on water quality, biological performance and nutritional profile of cultured fish. The mean temperature in all treatments was 23.09±0.8 ?C. DO and pH levels decreased from the beginning to the end of the study with the highest average found in the feed protein treatment of 22% (5.04±0.74 mg/L and 6.28±0.69), followed by 26% feed protein treatment (4.89±1.15 mg/L and 6.02±1.07), and 30% feed protein treatment (4.79±0.95 mg/L and 5.73±0.98). The lowest ammonium content (2.39±3.64 mg/L) was found in fish culture water with 22% feed protein content, followed by 26% protein content (2.93±2.52 mg/L) and 30% feed protein content (5.35±3.01 mg/L). Treatment of 26% feed protein content resulted in the lowest range of nitrite levels (1.43±1.59 mg/L), followed by 30% feed protein treatment (2.28±1.23 mg/L) and 22% feed protein treatment (3.22±1.52 mg/L). The highest average weight of fish (143.48±13.78 g), the highest daily growth rate (2.68±0.31%) and the lowest feed conversion ratio (1.45±0.19) was found in the feeding treatment with 30% protein content. Treatment of 22% protein content produced the highest survival rate (86.15%), while the highest biomass (6912.88±2586.17 g) was obtained from 26% feed protein treatment. There were significant differences (p<0.05) in absolute growth and daily growth rates between feed protein treatments 22% and 26% and between feed protein treatments 22% and 30%. There were no significant differences in other parameter. Based on the results of the nutritional profile analysis, the highest protein content (20.68%) was obtained in the 30% feed protein treatment. The highest fat content was produced by the treatment of 22% feed protein, (1.89%). Variations in feed protein content resulted in significant differences in the amino acid and fatty acid profile of fish. The highest value of most of the essential amino acids was obtained in the 26% feed protein treatment (L-Phenylalanine: 12.44 g/kg; L-Histidine: 7.18 g/kg; L-Isoleucine: 9.59 g/kg; L- Leucine: 16.47 g/kg; L-Threonin: 12.47 g/kg; L-Valine: 11.96 g/kg). The highest value of polyunsaturated fatty acid profiles was found in the 30% feed protein treatment (EPA: 0.0068%; DHA: 0.0936%; AA: 0.0502%), while for the lowest saturated fatty acids (0.3481%) was found in 26% feed protein treatment. Overall it can be concluded that the use of feed protein content of 26% and 30% was the most recommended in the biofloc system of tilapia culture. The 26% feed protein treatment gave the best results for water quality and amino acid profile, while 30% feed protein gave the best results for growth and fatty acid profile.